Aeschylus' Aetnaeans, The Palici and Cultural Politics in Deinomenid Sicily. (November 2019) - Thatcher, Mark
Abstract: This paper re-evaluates the role of the Palici, a pair of indigenous Sicilian deities, in Aeschylus' fragmentary tragedy Aetnaeans . Past readings of this play focus on 'linguistic colonialism', through which Greeks took possession of native gods and thereby demonstrated their cultural superiority. By contrast, this analysis situates the play within more nuanced models that envision cultural contact as a two-way process and highlight the diversity inherent within the categories of 'Greek' and 'Sikel'. By reading the play in its fifth-century Sicilian context, particularly in light of new archaeological discoveries at the sanctuary of the Palici (Rocchicella di Mineo), this study establishes that – although the play does constitute a form of cultural imperialism – nonetheless we can gain more from focusing on the play's politics of negotiation and accommodation, rather than appropriation and displacement. A reassessment of three aspects of the Aetnaeans – the birth of the Palici, their parentage and the play's multiple settings – shows that Aeschylus had access to reliable information about the Palici and reworked it in his play in order to develop a new and uniquely Sicilian cultural synthesis in which indigenous deities play an important role.